Open innovation and the challenges of human resource management - Lenz, Sabrina (2014)
This paper considers challenges of Human Resource Management (HRM) in Open Innovation processes. It examines which strategies managers used to overcome these problems in the case of the Brazilian Oil and Gas company Petrobras. By conducting an inductive case study it develops a contextual model based on the use of grounded theory. It argues that the most important categories were to overcome problems of (a) the interpersonal relationship, (b) power shifting inside the organization, and (c) making people more valuable to the organization and shows how managers tackled these challenges. It contributes with a deep analysis of HRM challenges in Open Innovation that is important for a better understanding of management problems that can come along with Open Innovation processes.